Antioxidant Activity of Extracts of Soursop (Annona muricata L.) Leaves, Fruit Pulps, Peels, and Seeds - Hakime Hülya Orak; Ilayda Sevik Bahrisefit; Temine Sabudak (Polish Journal of Food and Nutrition Sciences)
The total phenolic content (TPC), total flavonoid content (TFC), and the antioxidant activity of soursop ( Annona muricata L.) leaf, fruit pulp, seed, and peel extracts obtained using successive extraction with hexane (Hxn), dichloromethane (DCM), ethyl acetate (EtOAc), and methanol (MeOH) were determined. The Hxn soursop seed extract was analysed by GC-MS. The highest TPC was determined in MeOH extracts. MeOH and EtOAc extracts were rich sources of flavonoids. Generally, soursop leaf and fruit pulp extracts had the highest and the lowest both TPC and TFC, respectively. Fatty acids were dominant in the Hxn seed extract. Among antioxidants, terpenoids ((E)-nerolidolas as dominant) and phytosterols ((3-β)-stigmast-5-en-3-ol with high content) were identified. The soursop seed, followed by leaf and peel extracts (MeOH and EtOAc) had the highest DPPH• scavenging activity, TEAC, FRAP, and CUPRAC. Antioxidant activity of peel extracts (MeOH and EtOAc) was particularly high in β-carotene-linoleic acid emulsion system. Strong correlations were found between TPC, TFC, TEAC, FRAP, and results of DPPH assay. In conclusion, soursop leaves and fruit seeds and peels, which are cheap, waste plant material, could be considered as a source of phenolic antioxidants with a high antioxidant activity. Antioxidant activity of peel extracts (MeOH and EtOAc) was particularly high in β-carotene-linoleic acid emulsion system. The strong correlations between TPC, TFC, TEAC, FRAP and results of DPPH assay were found. In conclusion, soursop leaves and fruit seeds and peels, which are cheap, waste plant material, could be considered as a source of phenolic antioxidants with high antioxidant activity.